A new method for suppressing nonlinear flutter and thermal buckling of composite lattice sandwich beams - Chai, Yuyang; Li, Fengming; Zhang, Chuanzeng (Acta mechanica, 2022)
Pre-stresses or axial loadings induced by deformations of adjacent structures, edge constraints or mounting inaccuracies and elastic supporting components attached to one side of the sandwich structures may affect the aerothermoelastic stability, which is an important subject in the design of supersonic aircraft. Therefore, the nonlinear flutter and thermal buckling behavior of composite lattice sandwich beams with translational springs under axial loading in supersonic airflow is investigated in this paper. In the structural modeling, the von Kármán large-deflection theory is applied to establish the stain–displacement relations. The aerodynamic pressure is evaluated by the supersonic piston theory. The differential equations of motion are obtained by Hamilton’s principle and the assumed mode method. The highlight of this study is that a new approach for limit cycle oscillation (LCO) suppression and thermal buckling elimination without changing the stiffness of the lattice sandwich structure is proposed by utilizing the axial loading and translational springs. The structural natural frequencies are obtained and compared with reference results in the literature. The influences of the axial loading and the translational springs on the nonlinear supersonic flutter and thermal buckling properties of the sandwich beams are analyzed. Numerical results indicate that the present method is effective for nonlinear flutter suppression, and the thermal buckling effect can be completely eliminated by adjusting the axial loading of the sandwich beams.